A post Keynesian theory for Tobin's q in a stock-flow consistent framework. Issue 2 (2nd April 2016) - Bernardo, Javier López; Stockhammer, Engelbert; Martínez, Félix López
ABSTRACT: The paper proposes a post Keynesian framework to explain Tobin's q behavior in the long run. The theoretical basis is informed by the Cambridge corporate model originally proposed by Kaldor (1966 ), which is reinterpreted here as a theory for q. The core of the "Kaldorian q theory" is a negative long-run relation between q and growth rates, a negative relation between q and propensities to consume, and the fact that q can be different from 1 in the long-run equilibrium. We generalize this model through a medium-scale stock-flow consistent (SFC) model, which introduces important post Keynesian aspects missing in the Kaldorian model, such as endogenous money, a financial system, and inflation. We extend the model to include a more realistic treatment of firms' financial structure decisions and allow the interdependence between these decisions and dividend policy. Numerical simulations confirm that the original Kaldorian relations between q and growth rates and propensities to consume hold, but unlike the original model, in our model, q is not independent of how firms finance their investment. We also confirm the possibility of q being different from 1 in the long run. Finally, we contrast this "post Keynesian q theory" with the Miller–Modigliani dividend irrelevance proposition and the neoclassical investment and financial theory. It is shown that its validity depends crucially on the value taken by q : for q values different from 1 the proposition will not hold and dividend policy will be relevant for equity valuation. Therefore, post Keynesian q theory stands against the main predictions of mainstream finance and constitutes an alternative for developing a macroeconomic theory for equity markets.